Changes in Major Compounds during the Manufacturing of Rehmanniae Radix Preparata - Mun, Seo Young; Jeon, Se Hee; Kim, Jong Hyuk; Ha, Ju Hyeon; Cho, Seung Han; Kim, Ye Rin; Lee, Yeon Ju; Kang, Chang Keun; Rho, Il Rae (Journal of Agriculture & Life Science, 2025)
This study examined the effects of pre-soaking solvents and repeated steaming-drying (SD) cycles on the antioxidant activity and active compound content of Rehmanniae Radix Preparata(RRP), the processed root of Rehmannia glutinosa Libosch. SD treatments were conducted for 1 to 9 cycles using four different pre-soaking solvents: Takju (a traditional rice wine), Spirits, Honey, and Sugar solution. The results showed no significant differences in DPPH and ABTS radical scavenging activities or in total polyphenol and flavonoid contents among the pre-soaking treatments, although samples pre-soaked in honey and Takju exhibited slightly higher levels. Polyphenol and flavonoid contents increased progressively with the number of SD cycles, reaching levels 2–3 times higher after nine cycles. Catalpol content remained relatively constant regardless of treatment, whereas aucubin content increased in all groups, with the highest accumulation observed in the Takju treatment. Similarly, 5-hydroxymethylfurfural (5-HMF) content increased with the number of SD cycles, with the highest levels found in the honey group, followed by Takju, Sugar, and Spirits. In conclusion, while the type of pre-soaking solvent had minimal influence on antioxidant activities and catalpol content, both aucubin and 5-HMF contents increased with additional SD cycles, with Takju proving particularly effective in enhancing their accumulation. KCI Citation Count: 0